Heterogeneity of differential atmosphere perception and its relationship with organizational silence among Chinese nurses: a cross-sectional study using latent profile analysis - Bai, Qiaoli; Bai, Yaping (Frontiers in Psychology, 2025)
ObjectiveTo probe the heterogeneity and the influences of clinical nurses’ perceptions of differential atmosphere, and to investigate the relationship between each profile of differential atmosphere perception and organizational silence.MethodsWe adopted the General Information Questionnaire, the Differential Atmosphere Scale, and the Nurses’ Organizational Silence Assessment Questionnaire to survey 523 clinical nurses in three tertiary general hospitals in Shaanxi Province. And we estimated the potential categories of clinical nurses’ differential atmosphere perceptions via latent profile analysis, and quantified the influences on each profile via χ2 and logistic regression analyses, and probed the differences in the organizational silence scores of individuals with three differential atmosphere perception profiles through the least significant difference (LSD) method.ResultsThe differential atmosphere perception of clinical nurses was divided into “Insiders” (16.25%), “Go-betweens” (57.55%), and “Outsiders” (26.20%). Monthly income and years of working experience were the influencing factors of different categories of nurses’ differential atmosphere perceptions. There was a significant difference on the total organizational silence score and on the three profiles (p < 0.001), specifically, “Outsiders” > “Go-betweens” > “Insiders.”ConclusionThis study has identified three distinct subgroups in the differential atmosphere perception of nurses and their influencing factors. The findings demonstrated the heterogeneity among the clinical nursing population. Nursing managers may take prompt and targeted measures to reduce differential atmosphere perception, so as to improve the development of the nursing team.